War by other means : building complete and balanced capabilities for counterinsurgency : RAND counterinsurgency study, final report - Gompert, David C.; Gordon, John, 1956-; Grissom, Adam.; Frelinger, Dave.; Jones, Seth G., 1972-; Libicki, Martin C.; O'Connell, Edward; Stearns Lawson, Brooke; Hunter, Robert Edwards, 1940-; International Security and Defense Policy Center; National Defense Research Institute (U.S.); Rand Corporation; et al. (Santa Monica, CA : Rand Corp., 2008)
The difficulties encountered by the United States in securing Iraq and Afghanistan despite years of effort and staggering costs raises the central question of the RAND Counterinsurgency Study: How should the United States improve its capabilities to counter insurgencies, particularly those that are heavily influenced by transnational terrorist movements and thus linked into a global jihadist network? This capstone volume to the study draws on other reports in the series as well as an examination of 89 insurgencies since World War II, an analysis of the new challenges posed by what is becoming known as global insurgency, and many of the lessons learned in Iraq and Afghanistan. The report's recommendations are based on the premise that counterinsurgency (COIN) is a contest for the allegiance of a nation's population; victory over jihadist insurgency consists not of merely winning a war against terrorists but of persuading Islamic populations to choose legitimate government and reject violent religious tyranny. The authors evaluate three types of COIN capabilities: civil capabilities to help weak states improve their political and economic performance; informational and cognitive capabilities to enable better governance and improve COIN decisionmaking; and security capabilities to protect people and infrastructure and to weaken insurgent forces. Gompert and Gordon warn that U.S. capabilities are deficient in several critical areas but also emphasize that U.S. allies and international organizations can provide capabilities that the United States currently cannot. The authors conclude by outlining the investments, organizational changes within the federal government and the military, and international arrangements that the United States should pursue to improve its COIN capabilities.
Defining the Problem -- Framing the Problem -- Countering Type III Insurgency -- Overview of Capabilities Needed to Counter Type III Insurgency -- Civil Capabilities -- Information Capabilities -- Perception and Cognition -- General Security Capabilities -- Local Security Capabilities -- U.S. Security Capabilities -- Multilateral Counterinsurgency -- Investment Priorities -- Organization: Unsettled Structures for Unsettled Times -- Implications and Recommendations -- Appendix A: Eighty-Nine Insurgencies: Outcomes and Endings -- Appendix B: Multilateral COIN Capacity -- Appendix C: Indicators and Warnings -- Appendix D: Ground-Force Tasks and Improvements.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 445-453).
Also available on the internet via WWW in PDF format.
Keywords: Counterinsurgency -- United States; Institution building -- Government policy -- United States; Insurgency; Islamic fundamentalism -- Political aspects; Security, International -- 21st century; Strategy; Terrorism -- Prevention; United States -- Foreign relations -- 2001-; United States -- Military policy -- 21st century